Semantic and Phonemic Verbal Fluency Performance in Patients with General Anxiety Disorders and Allostatic Load under Alprazolam Treatment - Soria, Carlos Alberto (2019)
Purpose: Anxiety disorders are frequently associated with chronic stress with possible cognitive consequences. The aim of this study was to determine the verbal fluency performance in a cohort of patients with anxiety disorders and allostatic load, treated with alprazolam during 12 weeks. Methods: Patients with GAD (general anxiety disorders, DSM IV), with >6 in Hamilton Anxiety Rating Scale (HAM-A), neuroticism > 18 (NEO-FFI inventory), and normal Mini-Mental State Examination were included. Clinical and Psychiatric examination, Allostatic Load Index and cognitive assessment were analyzed before and after 12 weeks of treatment. The phonemic and semantic verbal fluency tests were determined in all patients. The scoring for each fluency task was determined by counting the number of correct words. The total score from each semantic and phonemic verbal task was analyzed comparing the individual score with normal data controlled by age and sex. Patients with scores > −2 standard deviation (SD) from normative data were considered impaired. Results: Fifty-four patients completed the semantic verbal fluency test before treatment and fifty patients completed after treatment. According to the z-scores before treatment 7 patients of 54 (12.9%) had verbal fluency impairments. After treatment none patients showed semantic verbal fluency deficits but 3 patients of 50 (6%) showed phonemic impairments. Impaired group was significantly associated with an older age before treatment (p = 0.033) and with a similar tendency but not significant (p = 0.09) after treatment (Student t test). Conclusion: In this study older age factor was associated with verbal fluency impairment in GAD patients. Stratified treatments.